Exploration of Methadone and HIV Treatment For Injecting Drug Users In West Java, Indonesia: Lessons from Practice - Laere, Igor van; Hidayat, Teddy; Wisaksana, Rudi (Global Medical & Health Communication (GMHC), 2013)
ABSTRACT Over the last decade, Indonesia became one of the fastest growing injecting drug user (IDU) driven HIV epidemics in Asia. Among strategies to prevent and control the HIV epidemic in Indonesia, methadone maintenance treatment (MMT) has been established and could become an entry point for HIV testing and treatment in IDUs. This study explored MMT and HIV treatment practices in West Java. An evaluation team visited six MMT clinics, interviewed staff and collected data on patient characteristics, methadone dose, and HIV testing and treatment practices. By October 2011, from 203 IDUs entering MMT (range 7-73 per clinic), 95% were male with the average age of 31 years (range 19-60 years), 92% had a senior high school or higher diploma, 47% had a regular income, and 55% were married. The mean methadone dose was 79 mg/day (range 13-208mg/day). About 85% of the MMT patients were tested for HIV, of whom 70% were found HIV positive (121/173), while 59% had a baseline CD4 count > 200 cells/mm3 and 65% were receiving ART.Â  In conclusion, few IDUs entered MMT in West Java and among those who did; high HIV and ART rates were reported, stressing the need for active linking between harm reduction services and integrated MMT and HIV treatment for IDUs. Â  Key words: injecting drug user; methadone; HIV; ART; clinical guideline; Indonesia